Peningkatan keterampilan membaca pemahaman dengan menggunakan strategi directed reading thinking activity (drta) kelas v pada mata pelajaran bahasa indonesia - Rizky Fuad Andreansa; Sadiman Sadiman; Yulianti Yulianti (Universitas Sebelas Maret, 2019)
Abstract. This research purposed to increase the reading comprehension skill by using the DRTA strategy on students class V SDN Bibis Wetan student year 2018/2019. The form of this research was Classroom Action Research (CAT) held in two cycles. Everycycle was consist of 4 steps as following planning, action, observe, and reflection. The subject of this research was teacher and students was amounts 36 students. The technique of collecting datas were documentation, observation, interviewing, and test. The datas were analysed by using interactive analysis (Miles and Huberman). The data validity used source triangulation and technical triangulation. The result of this research, there was an improving the reading comprehension skill after the teacher used DRTA strategy on student. Keywords: Directed Reading Thingking Activity (DRTA), Reading Comprehension Skill, Elementary School